DAMPAK EKONOMI DAN SOSIAL PADA TRADISI SYAWALAN DI KELURAHAN KRAPYAK KOTA PEKALONGAN - Dina Amalia Mahmudah (Fakultas Ekonomi Universitas Pekalongan, 2020)
This research aimed to know the impact of Syawalan Tradition in Krapyak Pekalongan City to its native Krapyak society. Syawalan is one of the oldest tradition in Pekalongan City. It was interesting did this reserach because nowdays the society more aware to culture. The data were collected using interview and questionnaire. There were 100 respondents tho are lived in Krapyak. The difficulties of this research was to intervier with eldest. The data analysis using descriptive statistical analysis. The result of this research showed that Syawalan gave more economics impact than social impact to its native Krapyak Society. Keywords: Tradition, Culture, Social life, Economic Life, Local culture.